Surgical and endoscopic management of a pericardioesophageal fistula after radiofrequency pulmonary vein isolation. Issue 11 (3rd July 2020) - Siroky, Gregory P.; Niazi, Kareem; Ghaly, Aziz; Kahaleh, Michel; Tyberg, Amy; Langenfeld, John; Kostis, William J.; Kassotis, John; Coromilas, James; Saluja, Deepak
Abstract: Introduction: The most feared complication of pulmonary vein isolation (PVI) is an atrioesophageal fistula (AEF). While rare (0.1‐0.25%), primary surgical closure (as opposed to esophageal stenting) is associated with lower mortality. Pericardioesophageal fistula (PEF) may present prior to fistulization into the atrium. Unfortunately, data on the optimal management of PEFs are lacking. Case report: Seventy‐one‐year‐old male with AF presented with chest pain 3 weeks after radiofrequency PVI. Computed tomography angiography (CTA) chest and echocardiogram showed pneumopericardium. Barium esophagram showed extravasation from esophagus into the pericardium without connection to the left atrium. Sternotomy with mediastinal exploration exposed the pericardial defect, over which a CorMatrix patch was placed. The fistula was then stented endoscopically with endosuture fixation. Poststent esophagram did not show barium leak, and the patient was discharged home. One week later, the patient returned with enterococcal and candida bacteremia and an acute right parietal/occipital lobe infarct. Barium esophagram showed contrast extravasation into the pericardium. The patient rapidly succumbed to his illness and died. Autopsy revealed pericardial abscess posterior to the LA in communication with the esophagus. Extension to the LA was not seen. Conclusion: While the surgical treatment of AEF is relatively well established, there is no consensus in the management of PEF. While prior small series have suggested PEF may be managed with esophageal stenting, our case illustrates the limitations of this approach.